Mapping the Landscape of Organized Sport in a Community: Implications for Community Development - Doherty, Alison; Patil, Swarali; Robar, Justin; Perfetti, Abby; Squire, Kendra (Frontiers in Sports and Active Living, 2022)
This study presents the landscape of private community sport organizations in the City of London, Ontario, Canada based on a profile of organizational features that align conceptually with critical aspects of community development. Features representing the scope – variety of sports offered, program age targets, and other offerings – and operations – nonprofit/commercial sector, open/closed program type, independent/affiliated/franchise status, and shared/exclusive facility use – of community sport organizations were captured from publicly available information about the population of 218 organizations. The location of sport delivery points for each organization was also mapped. The landscape is characterized by a balance of nonprofit and commercial organizations, offering a wide variety of sports, across all ages and City districts, but predominantly offered through closed programming that typically requires an extended financial commitment. Community sport organizations in this city are also most likely to operate independently, and share facilities. These features, and the landscape, are conceptualized as having implications for access, social inclusion, engagement and citizenship, and social capital that are fundamental to community development. Mapping the landscape in this community provides a valuable resource for understanding that potential.